Anxiety in Speaking Japanese Experienced by the Department of Japanese Language Education Students of Unnes - Lispridona Diner (Journal of Japanese Language Education and Linguistics, 2023)
Language learners, particularly foreign language learners, endure language anxiety. Language anxiety can affect learners at all levels, including early, intermediate, and advanced. Anxiety in speaking Japanese is quite noticeable in speaking abilities. It happens for Japanese language students enrolled in the Japanese language education study program as well. The causes of anxiety in speaking Japanese can be seen in a variety of ways, including vocabulary knowledge, sentence patterns, confidence level, and so on. The objective of this research is to discover how worried Japanese people are and what causes their worry. This study's subjects were Japanese language students at the beginning and intermediate levels, each of levels had 50 students. This study took a qualitative approach and collected the data through observation and questionnaires. According to the study's findings, 60% of students at the beginning level did not sense anxiety when speaking Japanese, despite the fact that their worried behavior indicated linguistic anxiety. Scratching the head and moving the hands, for example. Meanwhile, 60% of middle-level students were afraid to speak Japanese because they lacked command of vocabulary and sentence patterns.